Temperature Control of Liquid Filled Tank System Using Advance State Feedback Controller - Kunal Chakraborty; Rahul Dev Basak; Indranil Roy; Sankha Subhra Ghosh (Institute of Advanced Engineering and Science, 2015)
In this paper modeling of a temperature measuring tank system has been done and then a Advance state Feedback Controller have been used for controlling the step responses of the system. The proposed system extends to a three tank system and each tank has same amount of liquid. The results of computer simulation for the system with Advance state Feedback is shown. DOI: http://dx.doi.org/10.11591/telkomnika.v14i2.7644